The Challenges And Risk Of Development Vocational Education In Indonesia - Mulyadi, Yadi; Sumarto, Sumarto (Journal of Technical Education and Training, 2009)
The quality of human resources (human resources) really depended on good and bad points of the educational agency that prepared him. By paying attention to this link, then the urgency of the quality educational agency had finally become the key strategy in order to gains the height of the quality of human resources. Vocational education that was quality became one of the most important answers for the Indonesian nation towards the demand of the globalisation. The quality of the graduate of Vocational Education that was high, required the adoption action and the adaptation of all the requirements for the work institution/the industry, furthermore reconciled the international standard of manpower, as well as filled the current legislation regulation. Vocational education aimed at increasing intelligence, knowledge, the identity, the noble moral, as well as participants’s skills educated to live independent and followed education further in accordance with the program Vocational education (Permendiknas No. 22 Th. 2006). There were two spectra of the territory that became the aim of Vocational Education, that is preparing participants educated to the world of the work and at the same time the academic world. Therefore, then the Vocational educational curriculum became more complex both planning and his implementation. In the Vocational educational curriculum the achievement was in two spectra of the territory, that his achievement through the application of the curriculum comprehensively. This curriculum it was hoped guaranteed fully the achievement from the aim of Vocational Education. Therefore, in his fact of Vocational Education needed the operational fund that was far more bigger than that was needed by middle education the public.